Development Professionalism Strategy in Lecturers Improve The Competitiveness of The Nation Through The Development of Science And Technology - Septi Fitri Meilana (ADI Journal on Recent Innovation, 2020)
Professionalism is a performance quality and at the same time as a demand for behavior professional in carrying out their duties. Professionalism. General understanding of professionalism demonstrate hard work in a trained manner without certain conditions. professionalism refers to the degree of one's appearance as a professional or appearance jobs as a profession, some have high, medium, and low professionalism. Professionalism also refers to the attitudes and commitments of professional members to work based on high standards and professional codes of ethics. Thus professionalism is a performance quality and at the same time as a demand for professional behavior in carrying out their duties. This is as a demand to shape human resources quality and high competitiveness in local, national and international forums. Some characteristics of professional lecturers include: (1) having a soul calling and idealism, (2) have educator qualifications, (3) have the required competencies, (4) have ties collegiality and professional code of ethics, (5) is responsible for carrying out the task professionalism, (6) get a decent income, (7) have the opportunity for professional development, (8) has guaranteed legal protection in running professional duties, (9) and have professional organizations that have authority to regulate matters related to his professional duties (Nani Setiawati in Iskandar, 2014). Then from as a lecturer must have a strategy to improve professionalism through the development of science and technology.